Mechanism of microRNA regulating the progress of atherosclerosis in apoE-deficient mice. Issue 2 (20th December 2021) - Lou, Xiaoqian; Wang, Dawei; Gu, Zehui; Li, Tengteng; Ren, Liqun
ABSTRACT: MicroRNAs play important roles in atherosclerogenesis and are important novel pharmaceutic targets in atherosclerosis management. The whole spectrum of miRNAs dysregulation is still under intense investigation. This study intends to identify more novel dysregulated microRNAs in atherosclerotic mice. Half of eight-week-old male ApoE-/- mice were fed with high-fat-diet for 12 weeks as a model mice, and the remaining half of ApoE-/- mice were fed with a normal-diet as a control. A serum lipid profile was performed with ELISA kits, and atherosclerotic lesions were assessed. Aortic tissues were dissected for gene expression profiling using a Multispecies miRNA 4.0 Array, and significant differentially expressed miRNAs were identified with fold change ≥ 2 and p < 0.05. Real-time quantitative PCR was used to validate microarray gene expression data on selected genes. Predicted target genes were extracted and subjected to bioinformatic analysis for molecular function and pathway enrichment analysis. Model mice showed a 15.32% atherosclerotic lesion compared to 1.52% in the control group. A total of 25 significant differentially expressed microRNAs were identified, with most of them (24/25) downregulated. Real-time quantitative PCR confirmed the GeneChip data. Bioinformatic analysis of predicted target genes identified high involvement of the PI3K/Akt/mTOR signaling pathway. Microarray profiling of miRNAs in high-fat-fed Model mice identified 25 differentially expressed miRNAs, including some novel miRNAs, and the PI3K/Akt/mTOR signaling pathway is highly enriched in the predicted target genes. The novel identified dysregulated miRNAs suggest a broader spectrum of miRNA dysregulation in the progression of atherosclerosis and provide more research and therapeutic targets for atherosclerosis.